From Carnival to Pious City: Scenes of Urban Life in Leandro Bassano’s The Months - Moldovan, Anca-Delia (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2021)
This work examines the urban environment depicted by Leandro Bassano in his cycle of the Twelve Months during February and March, and the notable iconographic shift it presents with respect to the typical imagery of farming labours. Leandro represented the themes of Carnival in February and Lent in March, breaking up this otherwise agricultural calendar to introduce the division of time according to civic and religious rhythms. It is argued that this transformation in iconography occurred at the intersection of the reformed Roman Missal and the emergence of the commedia dell’arte. Finally, this article explores what the dialogic relationship between Leandro’s February and March conveys about the deeper cultural and seasonal experience of the Veneto city in the post-Tridentine context.